2006
DOI: 10.1080/02652030500429117
|View full text |Cite
|
Sign up to set email alerts
|

Copper content of grape and wine from Italian farms

Abstract: The copper content of grape and wine from 16 wine-farms in Italy was studied during the harvest of 2003. The influence of the number of copper applications, the period between the last application and harvest, and the total amount of copper applied was examined. Of the total number of samples analysed, 13% of grape samples and 18% of wine samples exceeded the maximum residue level (MRL). The total amount of copper applied and the number of days between the last application and harvest explained 44% of the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 9 publications
0
55
1
2
Order By: Relevance
“…In addition, this study showed that the copper content did not depend on the strategy of pest control (conventional, integrated or organic). Of the three above factors, the most important is the amount of copper applied, since it implies about 50% of the final concentrations in grapes and wine (García-Esparza et al, 2006). Other researchers studied the possible effect of fermentation processes on the levels of total arsenic and inorganic species [As (III) and As (V)] and organic (arsonic monomethyl acid [MMAA] and dimethyl arsinic acid [DnaA]) in 45 wines of southern Spain.…”
Section: Processmentioning
confidence: 99%
“…In addition, this study showed that the copper content did not depend on the strategy of pest control (conventional, integrated or organic). Of the three above factors, the most important is the amount of copper applied, since it implies about 50% of the final concentrations in grapes and wine (García-Esparza et al, 2006). Other researchers studied the possible effect of fermentation processes on the levels of total arsenic and inorganic species [As (III) and As (V)] and organic (arsonic monomethyl acid [MMAA] and dimethyl arsinic acid [DnaA]) in 45 wines of southern Spain.…”
Section: Processmentioning
confidence: 99%
“…The residual concentration in musts resulted from fruit, or use of fungal treatments, is related to copper rate applied throughout growing season, the quantity of the applications, and the amount of rainfall between application and harvest [16]. The current legislation in South Africa considers in the legal parameters any concentration up to 20 mg L −1 Cu 2+ in the grape berries [17].…”
Section: Introductionmentioning
confidence: 99%
“…Li (1994) reported that in vineyards using Cu-based fungicides, extremely high Cu concentrations were observed in the leaves and petioles of the grapevines (all >118 mg kg −1 ), whereas the concentrations in the pulp of the berries (skin and seeds removed) ranged from 0.33 to 1.7 mg kg −1 FW. García-Esparza et al (2006) demonstrated that the amount of Cu applied via fungicides exhibited a low correlation (R 2 =0.26) with the metal residues in the grapes. The same study reported Cu concentrations in grapes ranging from 2 to 40 mg kg −1 FW, and after 50 days of fungicide application, the concentrations decreased to values below 10 mg kg −1 FW.…”
Section: Cu Concentration and Content In Grapevinesmentioning
confidence: 99%